2020
DOI: 10.1080/17441730.2020.1778854
|View full text |Cite
|
Sign up to set email alerts
|

Getting the measurement right! quantifying time poverty and multitasking from childcare among mothers with children across different age groups in rural north India

Abstract: Existing research suggests that women spend a disproportionate amount of time on unpaid housework and childcare compared to men. However, there is a lack of empirical evidence on unequal time burdens due to childcare among women. This study analyses the quantum of time poverty and multitasking behaviours of 3623 rural women with children of varying ages across rural North India. Findings show that mothers with infants spend more time on childcare and less time on self-care and leisure, and employmentrelated ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Similarly, past year employment among married Indian women aged 15–49 declined by 12 percentage points (from 43% to 31%) between 2005–06 and 2015–16 [ 39 , 44 ]. Time poverty amongst working women in India is particularly acute [ 45 , 46 ]. As a result of strong gender asymmetry in the division of domestic labor, most working women in India still spend a substantial amount of their time on housework and caring for their children [ 45 , 47 49 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, past year employment among married Indian women aged 15–49 declined by 12 percentage points (from 43% to 31%) between 2005–06 and 2015–16 [ 39 , 44 ]. Time poverty amongst working women in India is particularly acute [ 45 , 46 ]. As a result of strong gender asymmetry in the division of domestic labor, most working women in India still spend a substantial amount of their time on housework and caring for their children [ 45 , 47 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Time poverty amongst working women in India is particularly acute [ 45 , 46 ]. As a result of strong gender asymmetry in the division of domestic labor, most working women in India still spend a substantial amount of their time on housework and caring for their children [ 45 , 47 49 ]. Many women opt to withdraw from the labor force entirely in order to take care of their children, or alternately, choose an occupation that is more accommodating of their prescribed gender roles [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on gender equality and housework in Japan, Taiwan, and the United States Despite women's growing educational attainment and some legal progress in protecting women's rights in the three countries' labour markets, women still do most housework in Japan, Taiwan, and the U.S. (Inaba, 1998;Ishii-Kuntz, 2009;Matsuda, 2001;Nishioka & Yamauchi, 2017;Tsuya, 2000;Tsuya et al, 2005). In each of these three countries, women's disproportionate share of housework is especially pronounced among couples with young children (Bianchi et al, 2012;Cheng & Hsu, 2020;Irani & Vemireddy, 2021;Nakamura & Akiyoshi, 2015), which may be alleviated to an extent by assistance from women in their extended families (Hu & Kamo, 2007;Kang & Cohen, 2018;Takahashi et al, 2013). Nevertheless, in East Asia, the division of labour still adheres to the traditional model featuring male-breadwinner and female-homemaker households (Slote & De Vos, 1998); Japanese and Taiwanese men occupy the public sphere and participate in the market economy, and their cultures still pressure most married women to stay at home and to perform the majority of housework and childcare (Borovoy, 2005;Chen & Yi, 2005;Kato et al, 2018;Shirahase, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of biological parents of under 5 children, they observed an association between father's regular alcohol use and children's developmental delay mediated by less-skilled maternal parenting practices [ 13 ]. We postulate the increasing risk of harmful alcohol use over time can be due to their limited choice in the measures to relieve their stress, given their burden of house chores and childcare [ 18 ]. Especially for alcohol use, studies have shown gender differences in stress-related alcohol use: women are generally more likely to drink to regulate negative affect and stress reactivity while men may be more likely to drink for positive reinforcement [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the prevalence of harmful alcohol use in mothers of young children, we restricted our analysis to the data of biological mothers of under 5-year children. The first wave in 2008 included 2,150 mother-baby pairs and 81.6% of the primary sample was retained in the 4th wave study in 2011 [ 18 ]. Information about participants’ age, highest education, monthly income, employment status of the year, current smoking, harmful alcohol use and smoking of the partner, plan for additional childbirth, and parenting stress were obtained using self-administered questionnaires.…”
Section: Methodsmentioning
confidence: 99%